Fruit set and plant regeneration in cassava following interspecific pollination with castor bean - Baguma, J.K.; Mukasa, S.B.; Kawuki, R.S.; Tugume, Arthur K.; Buttibwa, M.; Nalela, P.; Eyokia, M.; Oshaba, B.; Ceballos, Hernán; Lentini, Zaida; Baguma, Y. (African Journals Online, 2019)
The increasing demand for cassava (Manihot esculenta Crantz) for food and non-food uses in the tropics necessitates that its breeding for increased root productivity be made faster. The characteristic long breeding cycle and heterozygous nature of this crop, pose a major obstacle to its rapid genetic improvement. This study aimed at inter-pollinating cassava with castor bean (Ricinus communis), with a purpose of inducing and regenerating cassava doubled haploids (DHs). A total of 3,349 flowers from twelve elite cassava varieties were inter-pollinated with caster bean. A total of 803 fruits were harvested for early embryo rescue and/or ovule culture. Of these, three were dissected to obtain seven unique embryos, while 800 were dissected to obtain 1312 young ovules, all of which were cultured in vitro. Overall, 82 (6.25%) of the cultured ovules formed callus that originated from the embryosac region, which is haploid. Four out of seven rescued embryos (57.1%) regenerated into plantlets. Ploidy analyses of 24 samples using flow cytometry revealed that 23 of the analysed samples were diploid. However, one callus sample was anueploid. Only one sample had an exceptionally high level of homozygosity ( 84.2%). These findings lay a foundation for future research aimed at induction of haploids in cassava.